Solar electricity for sustainable development: Cost determinants in the Global South - Jose Antonio Ordonez; Felix Fink; Vasilios Anatolitis; Wolfgang Eichhammer (Fraunhofer-Institut für System- und Innovationsforschung ISI, 2022)
Complying with the goals of the Paris Agreement on climate protection will require a substantial decarbonization of the global energy system by the second half of the century. Developing countries and emerging economies already account for more than half of global energy related emissions. Strong economic and demographic growth in these countries will drive future power sector expansions. At the same time, solar photovoltaics has experienced massive cost reductions in recent years. Despite substantially lower demand growth for electricity and comparably lower solar potentials, eight out of ten countries with the largest additions of solar PV installations in the last decade are highly developed countries. In this paper, we analyze the perspective towards solar PV integration by country development level. We firstly apply Kaya decomposition analysis to analyze emission dynamics by country groups. We find renewable energies to play a minor role in countries of low human development. Combining financing data and country specific solar irradiation potentials, we find that for many countries in the Global South, comparably inferior financing conditions overcompensate the higher irradiation potentials, making capital intensive renewable energy projects unviable. Our results highlight the importance of access to affordable finance for capital intensive renewable energy technologies, such as solar PV, and suggest that climate policies in countries of low human development should more decidedly focus on reducing risk premiums, if these are to represent an economically viable option for climate mitigation.
Keywords: 330; LCOE; Solar PV; Energy and development; Renewable cost reductions; Technology learning; Kaya identity